Size effect on optical conductivity of Bi2Te3 nanoparticles due to softening of phonon frequencies. (2022) - Choudhary, K.K.; Rathore, Vinod; Dixit, R.C.
Abstract: The frequency-dependent optical conductivity σ(w) strongly depends on the particle size in nanostructures. Phonon frequencies are believed to be decrease on a decrease in particle size due to the softening of phonon frequencies around grain boundaries in nanomaterials. The optical conductivity of Bi2 Te3 nanoparticles is studied using the two components model: First is the coherent motion of Drude electrons within the Bi2 Te3 nanoparticles, and second is the incoherent hopping of charge carriers from one Bi2 Te3 nanoparticle to another. The model has the phonon frequency and relaxation rates as the independent free parameters, which depend on nanoparticle size. The relaxation rates that are a function of frequency are incorporated in optical conductivity through memory functions. The coherent motion of Drude carriers exhibited a peak in intensity near zero frequency regime and decreased to a minimum value in the far-infrared region. The incoherent hopping of electrons from one Bi2 Te3 nanoparticle to another produces a broad peak in the frequency-dependent optical conductivity at around the mid-infrared region. On decreases in nanoparticle size, softening of phonon frequencies occurs at interfaces due to an increase in interface volume ratio; as a result, the peak in optical conductivity at the mid-infrared region shifts towards lower frequencies.